Changes in bone quality after switching from a TDF to a TAF based ART: A pilot randomized study - Soldado-Folgado, Jade; Rins-Lozano, Oriol; Arrieta-Aldea, Itziar; Gonzále-Mena, Alicia; Cañas-Ruano, Esperanza; Knobel, Hernando; Garcia-Giralt, Natalia; Güerri-Fernández, Robert (Frontiers in Endocrinology, 2023)
Background: The impact of tenofovir disoproxil fumarate (TDF) antiretroviral (ART) regimens on bone health has been characterized mostly by bone mineral density (BMD), but recently also by bone quality (BQ). The aim of this pilot study is to assess the changes in BMD and BQ after switch from TDF to tenofovir alafenamide (TAF) ART. Methods: HIV individuals receiving TDF-based ART were randomized to switch to Bictegravir-TAF-Emtricitabine or to remain in the same regimen.At baseline and 24-weeks after randomization, participants underwent BMD by DXA and BQ assessment using bone microindentation,a technique that measures bone quality expressed as bone material strength index (BMSi).A panel of plasma bone turnover biomarkers were measured by ELISA at the same time-points.Values are expressed as median [interquartile range] and non-parametric tests were used where appropriate. Results Twenty-four HIV individuals were included,19 were men (80%).Median age was 43 years (IQR 38-54).Half of individuals were allocated in the TDF group while the other half changed to TAF treatment.No differences at baseline between both groups were detected. Non-significant changes nor in lumbar or femoral BMD at week 24 was found in any regimen. In contrast, there was an increase in BMSi in the TAF arm at 24 weeks, and thus an improvement in BQ[81.6 (79-83) to 86 (80-88) (+5.1%);p=0.041], whereas the TDF arm remained stable from 82 (76-85) at baseline to 82 (73-83);p=0.812. Hence, at week 24 there were significant differences in BQ between arms (p=0.049). A reduction in bone formation markers was found at week 24 in both regimens: N-terminal propeptide of type-1 collagen decreased a 20% (-35 - -0.6);p=0.031 with TAF and -16%(-25 - -5);p=0.032 with TDF.Also a decrease in bone resorption marker C-telopeptide with TAF was detected [-10% (-19 - -5);p=0.028] but not with TDF (p=0.232),suggesting a less metabolically active bone after switching to TAF. Conclusions: A bone quality improvement was found after switching from a TDF to a TAF based ART independently of BMD, suggesting that the bone health benefits of TAF may extend beyond BMD. Future research should be directed to confirm these findings and to identify the underlying mechanisms of ART related bone toxicity.